2017
DOI: 10.1007/s00192-017-3446-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the outcome of surgery for pelvic organ prolapse

Abstract: Introduction and hypothesisPelvic organ prolapse (POP) surgery is a common gynecological procedure. Our aim was to assess the influence of obesity and other risk factors on the outcome of anterior and posterior colporrhaphy with and without mesh.MethodsData were retrieved from the Swedish National Register for Gynecological Surgery on 18,554 women undergoing primary and repeat POP surgery without concomitant urinary incontinence (UI) surgery between 2006 and 2015. Multivariate logistic regression analyses were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 28 publications
2
27
0
1
Order By: Relevance
“…Our findings were similar to those of previous studies which found no difference in post-operative outcomes between patients with and without obesity after digestive tract surgery [10,48,59,60], gynecologic surgery [61,62], vascular surgery [63,64], neurosurgery [9], or orthopedic surgery [12,65,66], even among those admitted in intensive care unit [67]. In most of these studies, a minimal invasive surgical method was used like in studies included in the current meta-analysis, allowing less Elsewhere, an increased risk of morbidity in postoperative period in patients with obesity has been widely documented in recent years in both oncology and nononcology surgery.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings were similar to those of previous studies which found no difference in post-operative outcomes between patients with and without obesity after digestive tract surgery [10,48,59,60], gynecologic surgery [61,62], vascular surgery [63,64], neurosurgery [9], or orthopedic surgery [12,65,66], even among those admitted in intensive care unit [67]. In most of these studies, a minimal invasive surgical method was used like in studies included in the current meta-analysis, allowing less Elsewhere, an increased risk of morbidity in postoperative period in patients with obesity has been widely documented in recent years in both oncology and nononcology surgery.…”
Section: Discussionsupporting
confidence: 92%
“…A study published in 2018 by Bohlin et al reported on factors influencing outcomes of anterior and posterior vaginal wall prolapse surgery, based on data from the GynOp register. 117 Patients were considered "cured" if they reported vaginal bulging sensation "never", "hardly ever" or "1-3 times per month" at 1 year after surgery (we categorized 1-3 times per month into "non-cured"). Recently published studies have shown that factors associated with prolapse recurrence are: preoperative degree of prolapse, 118,119 levator ani injuries, 119,120 family history, 119,120 age (inverse correlation), 120 BMI, 117,120,121 parity, 118 co-morbidities 118 and preoperative degree of bulging symptoms 117 .…”
Section: Post Publication Sensitivity Analyses Of Study Imentioning
confidence: 99%
“…We initially chose to categorize 1-3 times per month into treatment failure, whereas Bohlin et al categorized this into "no prolapse". 117 One could also question the choice of vaginal bulging being our primary outcome when assessing cure after posterior colporrhaphy, since vaginal bulging might not be as specific for women with posterior prolapse. Common problems associated with a rectocele are symptoms related to obstructive defecation.…”
Section: Selection Bias and Misclassificationmentioning
confidence: 99%
“…BMI was calculated by dividing body mass (in kg) by the square of height (m 2 ) and categorized as eutrophic, overweight and obese [19]. BMI was the anthropometric variable chosen because it is the most widely used variable in the literature to define overweight and obesity in women with PFMD [25][26][27][28]. Thus, comparisons between different populations could be performed.…”
Section: E T H O D Smentioning
confidence: 99%